2019
DOI: 10.1016/j.mayocp.2019.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Sea Change for Marine Omega-3s

Abstract: Recently, 3 large randomized controlled trials (RCTs) have assessed the effects of supplementation with marine omega-3 fatty acids on the occurrence of cardiovascular disease (CVD) events. We reviewed this evidence and considered it in the context of the large and growing body of data on the CV health effects of marine omega-3s. One RCT examining 8179 patients, most with coronary heart disease (CHD), reported that 4 grams/day of a highly purified omega-3 product containing eicosapentaenoic acid (EPA) reduced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 53 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…A recently published large scale RCT showing positive results with EPA supplementation met many of the suggestions put forth by Rice et al (87): (i) the EPA dose given (4 g/day) was ∼4-fold greater than other contemporaneous trials, (ii) the study had an average duration of 4.9 years, (iii) the baseline EPA levels were identical between the placebo and treatment group, and (iv) the plasma EPA content at 1 year was 5-fold higher than at baseline (90). This study, as well as other recent RCTs showing beneficial effects of ω-3 supplementation have been reviewed in detail by O'Keefe et al (91).…”
Section: Discussionmentioning
confidence: 88%
“…A recently published large scale RCT showing positive results with EPA supplementation met many of the suggestions put forth by Rice et al (87): (i) the EPA dose given (4 g/day) was ∼4-fold greater than other contemporaneous trials, (ii) the study had an average duration of 4.9 years, (iii) the baseline EPA levels were identical between the placebo and treatment group, and (iv) the plasma EPA content at 1 year was 5-fold higher than at baseline (90). This study, as well as other recent RCTs showing beneficial effects of ω-3 supplementation have been reviewed in detail by O'Keefe et al (91).…”
Section: Discussionmentioning
confidence: 88%
“…In contrast to generally consistent results from observational studies of circulating n-3 fatty acids and DHA, the effects of n-3 fatty acid supplementation on cardiovascular outcomes in RCTs have been mixed [4,6,[27][28][29][30]. The recent study, A Study of Cardiovascular Events in Diabetes (ASCEND) trial, of 15,480 individuals with diabetes free of prior CVD, which tested n-3 fatty acid supplementation (1 g/day) for 7.4 years, did not lower the risk of composite major vascular outcomes, while only vascular deaths were less frequent in the supplementation group than in the placebo group (RR 0.82 [95% CI 0.68, 0.98]) [31].…”
Section: Discussionmentioning
confidence: 92%
“…2 Over the ensuing 4 decades, intensive scientific investigation established the cardioprotective effects of EPA and DHA. 3,4 A meta-analysis of 14 prospective studies used food frequency questionnaires to estimate self-reported omega-3 PUFA intake among 514 483 individuals with 9065 strokes during follow-up. 5 Compared with the lowest omega-3 intake group in each study, individuals in the highest intake group had a 13% lower risk of total stroke and a 16% lower risk of fatal stroke.…”
mentioning
confidence: 99%